Behavior on Food Security Management of Students Following the Royal Sufficiency Economy Philosophy: A Case Study at Suratthani Rajabhat University - พรหมณะ, จารีย์; ปราณีธรรม, ชุลีวรรณ; ศักดา, ภรณ์พักตรา; เหล่าพราหมณ์, จุฑารัตน์ (Chophayom Journal, 2018)
The purposes of this research were (1) to study self-sufficiency economy practice of students from Suratthani Rajabhat University, (2) to study food security management behavior of students, and (3) to study factors related to self-sufficiency economy and factors related to food security management behavior of students. The population was 17,454 students from Suratthani Rajabhat University. The sample for this research was 391 students in Semester I, Academic Year 2016 collected by stratified sampling technique. Questionnaires were used for data collection. Frequency, percentage, mean, standard deviation, and Pearson’s product moment correlation were used to analyze the data. The results revealed that 1) self-sufficiency economy practice of students was at good level with an average of 3.62. 2) behavior in food security management of students was at good level with an average of 3.55. 3) self-sufficiency economy practice and food security management behavior were significantly positively correlated at .01 level. The results showed that age and education level had negative correlations with food safety management behavior of the students. Therefore, parents, teachers, and close relatives should take care of their children about food consumption and nutrition more closely. All sectors should publish and disseminate information and news about Sufficiency Economy Philosophy and way of life in accordance with the sufficiency economy continuously in order to provide students and all people with the correct knowledge and understanding until they can apply the principles of sufficiency to practice and apply in their daily lives properly. Keywords : Behavior, Food Security, Self-sufficiency Economy